DEVELOPING HALAL TOURISM IN AN ISLAND OF A THOUSAND MOSQUE: PROSPECTS AND CHALLENGES - Arifin, Achmad Zainal; Abdul Wahid (UIN Sunan Kalijaga, 2022)
One important aspect seems to be ignored in developing halal tourism concept is existence of non-Muslims surrounding the halal tourist destinations across the Island of Lombok. Moreover, there is no single definition of the concept of halal tourism. This paper argues that it is important to include fellow Hindus communities in Lombok to avoid negative consequences of developing halal tourism. This research employs a qualitative model, using in-depth interviews, participant observations and documentation methods. Focuses on Hindus communities in two regencies of Lombok Island, West Lombok and the city of Mataram, where many holy sites of Hindu are located and have a long history of relationship with Islam. Results indicate that there is not enough socialization of the concept of halal tourism for Hindus fellows. Some of them have similar idea with their fellows in Bali in rejecting the concept of halal tourism because they believe that halal tourism will affected their traditions and practices. Meanwhile, other Hindus seem to have a neutral position, meaning that they do not really understand about the concept of halal tourism but willing to support it, as long as they still have freedom in expressing their religious traditions and practices. These relatively negative opinions from Hindus communities have to be considered seriously by all related parties in developing halal tourism in Lombok as challenges to re-evaluate the concept of halal tourism to prioritize the Islamic values of moderation rather than economic and ideological oriented, including the use of more acceptable term of “Muslim-friendly tourist destination”.